FACTORS THAT AFFECTING BURNOUT IN INPATIENT NURSES AT THE HOSPITAL : LITERATURE REVIEW - Talkhah Afrizal; Indri Heri Susanti; Tri Sumarni (Bajang Institute, 2022)
Nurses are at the forefront of providing medical services to patients. This is due to the large number of nurses (50-60% of total workers) who are obliged to treat patients with a 24-hour system. This principle arises when a nurse is satisfied with her job in the hospital. The purpose of this study was to determine what factors affect burnout in nurses in hospital inpatient rooms. The method used in this study is a literature review. Objectivity, originality of research, and research contribution are some things that must be considered when selecting data sources.Objectivity, research authenticity, and contribution to research are some of the things that must be considered in the selection of data sources. In this research, the method used is secondary research methodology in the form of literature review with primary source. Population, Intervention, Compare, Outcome (PICO) approach is a data extraction method used for the data collection process. This study concludes that the frequency distribution is based on influencing factors such as the individual age factor (27.27%) with the most dominant age being 20-30 years, the most dominant gender being female (45.45%), education level the most dominant bachelor’s degree nursing care (27.27%), with the most dominant working period is < 5 years (27.27%), and the environment such as unsupportive medical equipment (18.18%) can affect the occurrence of burnout in nurses.